Gender and citation in two LIS e-journals : a bibliometric analysis of LIBRES and information research - Reece-Evans, Linsay (2021)
Through women outnumber men at a ratio of approximately 4:1 in the library and information science (LIS) field as a whole and 3:1 in academic librarianship, past studies suggest that male-authored LIS print journal articles outnumber female-authored articles both in number and in citations received. The amount of citations received can serve as an indication of status within the LIS profession and can affect chances for professional advancement. This study uses citation analysis to measure patterns of gender, authorship and citation within the LIS e-journals LIBRES and Information Research, and compares these results to Hakanson’s (2005) citation analysis of gender and citation patterns in three core LIS print journals. Results of this study suggest gendered affinity in citation and reference behavior. Findings include that from 1995-2007 more men than women published articles in LIBRES and Information Research; that both men and women referenced more male-authored articles; that men referenced male-authored articles at a greater rate than women referenced female-authored articles; that articles by women received more citations overall; and that men cited articles by men at a greater rate than they cited articles by women. Though female authorship was proportionately higher in the two LIS e-journals than in the three core LIS print journals, the imbalance in citation and reference patterns suggest that gender influences both male and female authors’ choice of references, as well as the amount of citations that authors receive.